Study on Use of Naked Barley (Hordeum vulgare var. Solu Uwa) Malt and Mold Bran as Enzyme Source for Preparation of Whisky - Acharya, Dev Raj; Adhikari, Babita (Journal of Food Science and Technology Nepal, 2014)
Naked barley (Hordeum Vulgare L.) of Solu uwa variety having highest &beta-amylase activity (645 unit/gdm), total soluble solid and fermentable nitrogen germinated at 15 ºC for 96 h and mold bran prepared from Aspergillus oryzae in wheat bran isolated from murcha having highest α-amylase activity (904 unit/gdm) incubated at 30 ºC for 168h were selected as enzyme source. Mold bran, naked barley malt and white maize flour (undertailed through 1.18×1.18 mesh size as substrate) were mixed to prepare four samples: 15% naked barley malt+ 85% maize flour (Sample A), 15% mold bran + 85% maize our (Sample B), 10% naked barley malt + 5% mold bran + 85% maize flour ( Sample C) and 5% naked barley malt+ 10% mold bran + 85% maize (Sample D). All samples were mashed separately to prepared wort, fermented using brewery yeast (Saccharomyes cerevisiae) to prepare beer and distilled to prepare whisky and compared with wort, beer and whisky prepared from mixture of 15% commercial barley malt and 85% maize our (Sample E). Total soluble solid, specific gravity, real extract, apparent extract, fusel oil, aldehyde, esters, titrable acidity, volatile acidity contents and sensory scores with respect to avor, mouthfeel after taste and overall acceptability were significantly better (p<0.05) in sample A than other samples B, C and D but comparable with sample E whereas fermentable nitrogen, viscosity, alcohol, original extract contents and real degree of fermentation were found signi cantly better in sample B. However, sensory scores of samples were signi cantly lower ( p< 0.05) in all samples than market whisky (Signature). Hence, without scarifying chemical and sensory scores sample D can be used to prepare whisky commercially. But harsh and pungent characteristics can be improved by maturation. DOI: http://dx.doi.org/10.3126/jfstn.v7i0.10597 J. Food Sci. Technol. Nepal, Vol. 7 (44-51), 2012